If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(5-3x)-4=152
We simplify the equation to the form, which is simple to understand
6(5-3x)-4=152
Reorder the terms in parentheses
+(+30-18x)-4=152
Remove unnecessary parentheses
+30-18x-4=+152
We move all terms containing x to the left and all other terms to the right.
-18x=+152-30+4
We simplify left and right side of the equation.
-18x=+126
We divide both sides of the equation by -18 to get x.
x=-7
| u/5+3=6 | | .45x=30 | | 3y+2=-1 | | -5(1+6n)-4=141 | | 5=ln(x+1)solve | | 4.3q-1.8-5.4q=2.1q-1.1 | | 2-y=-8-y | | 6+z/9=9 | | 3(d+9)=10(d+2) | | u/5+3=1 | | 8x+2=40 | | v/4-3=5 | | (8x-3)(9x+1)=0 | | 3m-n=2m+n | | 4(x+2)+1-2(x+4)=0 | | 4c^2-25= | | 0=-y+3 | | 16x^2+144x+144=0 | | C-R=P | | 12c^2-17cd-5d^2= | | C+R=P | | R-C=P | | x=16x^2+32x+19 | | 12c^2-17c+6= | | 2x=-7+3 | | 3u^2+8u-3= | | x=-16x^2+64x+192 | | 8a^2-48a+64= | | 5x+74=8x+41 | | 2x=76 | | y^2-4y-x+7=0 | | 0.4c-0.07+0.5c=0.11 |